2020
DOI: 10.1111/jfpp.15179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold plasma on avocado pulp (PerseaamericanaMill.): Chemical characteristics and bioactive compounds

Abstract: The effects of cold plasma on the enzymatic activity, color, bioactive compounds, and antioxidant activity of avocado pulp with lime extract (PL) and without extract (PW) were studied. The experimental conditions applied varied with regard to time (10, 20, and 30 min) and gas flow (10, 20, and 30 ml). The gas flow combination of 20 ml/20 min applied in PL was efficient for reducing POD and PPO activities and browning index as well as for color maintenance. Cold plasma increased the phenolic and carotenoid leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The other process parameter, gas flow rate (argon), unaffected the total phenolic content (Garofulić et al, 2015). In another study, Batista et al (2021) showed a synergistic impact of treatment duration and gas flow rate while processing avocado pulp with cold plasma. The total phenolic content of avocado pulp and avocado pulp supplemented with lime extract increased when the treatment time was raised at a specific gas flow rate.…”
Section: Effect Of Cold Plasma Treatment On Polyphenols and Phenolic ...mentioning
confidence: 98%
See 1 more Smart Citation
“…The other process parameter, gas flow rate (argon), unaffected the total phenolic content (Garofulić et al, 2015). In another study, Batista et al (2021) showed a synergistic impact of treatment duration and gas flow rate while processing avocado pulp with cold plasma. The total phenolic content of avocado pulp and avocado pulp supplemented with lime extract increased when the treatment time was raised at a specific gas flow rate.…”
Section: Effect Of Cold Plasma Treatment On Polyphenols and Phenolic ...mentioning
confidence: 98%
“…The positive impact of cold plasma exposure on the concentration of phenolic content in food matrices was reported by several authors. An increase in the phenolic content was reported in siriguela juice (Paixão et al, 2019), cashew juice (Rodríguez et al, 2017), Marasca cherry juice (Garofulić et al, 2015), allspice berries (Medvecká et al, 2020), turmeric powder (Hemmati et al, 2021), sugarcane juice (Manzoor et al, 2020), tomato pomace (Bao et al, 2020a), blueberry (Ji et al, 2020), avocado (Batista et al, 2021), grape pomace (Bao et al, 2020b), pitaya fruit (Li et al, 2019), tomato‐based beverage (Mehta et al, 2019), strawberry (Rana et al, 2020), and strawberry juice (Mehta & Yadav, 2020). The increase in the phenolic content was attributed to the reactive species generated by the cold plasma.…”
Section: Effect Of Cold Plasma Treatment On Polyphenols and Phenolic ...mentioning
confidence: 99%
“…Nonthermal techniques decrease the amount of PPO, resulting in the better maintenance of phenolic compounds [21]. Indeed, the reduction of PPO activity has a direct impact on the maintenance of polyphenols and could increase the recovery yield of polyphenols [28,132,135,136]. reported that raisins with a low PPO activity have a more quantity of polyphenols and accordingly have a richer nutritional value [137].…”
Section: Control Of Polyphenol Oxidase (Ppo) Using Mild Technologiesmentioning
confidence: 99%
“…This leads to the loss of PPO activity. As a result of this reduction, the phenolic content of the food matrix is not used as the substrate of enzymatic browning and could be extracted with better quality [28]. To the best of our knowledge, there is no research evaluating the impact of nonthermal technologies on PPO during the extraction process of polyphenols from food by-products.…”
Section: Control Of Polyphenol Oxidase (Ppo) Using Mild Technologiesmentioning
confidence: 99%
See 1 more Smart Citation